Manajemen Organisasi Pencak Silat Pagar Nusa Dalam Meningkatkan Spiritual Anggota Di Desa Bumi Serdang Kecamatan Tungkal Ilir Kabupaten Banyuasin - Maratus Solihah; Candra Darmawan; Lena Marianti (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to analyze the management of the Pencak Silat Pagar Nusa organization in improving the spirituality of its members in Bumi Serdang Village, Tungkal Ilir District, Banyuasin Regency. The focus of the study is directed at the planning, implementation, and evaluation of the development program carried out by the organization in shaping the spiritual values ​​of its members. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation of Pagar Nusa administrators and members. The results show that organizational management is carried out systematically through routine development, religious activities, and internalization of moral teachings as part of pencak silat training. Pagar Nusa has successfully implemented an integrated spiritual approach in every training activity, such as teaching prayers, strengthening morals, and instilling the value of discipline. These findings indicate that good development management can significantly improve the spirituality of members, while strengthening the religious identity and character of members in their daily lives. This study also emphasizes the important role of religious-based pencak silat organizations in the moral and spiritual formation of the younger generation at the village level.